Upaya Meningkatkan Kemampuan Guru Menggunakan Media Pembelajaran Pada Semester Juli-Desember 2021 Melalui Workshop di UPT SD Negeri 07 Kauman Kecamatan Rao Selatan Kabupaten Pasaman - Rosni Astamam (Laboratorium Program Studi Pendidikan Sejarah Universitas PGRI Sumatera Barat, 2022)
The purpose of this study is to gather data and examine initiatives made at UPT SD Negeri 07 Kauman Kec. South Rao, Kab. Passover, to enhance teachers' use of instructional media. This study is a school action research project that has two cycles, each of which has four stages: planning, carrying out, observing, and reflecting. Ten teachers served as the subjects of this study, which was carried out from July to December 2021 at UPT SD Negeri 07 Kauman Kec. South Rao, Kab. Pasaman. Techniques for gathering data that include field notes, observation sheets, and documentation. Utilizing percentages and data reduction, data were evaluated.The research's findings were presented at workshops on creating instructional materials that school principals held at UPT SD Negeri 07 Kauman Kec. South Rao, Kab. Passover to help teachers prepare instructional materials. This is characterized by an improvement in teachers' skill levels, which is seen in cycles I and II. In accordance with cycle 1, the teacher's capacity to set up instructional media for use during the teaching and learning process is still considered sufficient and good. only 50% Based on cycle II, the teacher's capacity to put together educational materials is already in the very good category. As a result, the percentage of instructors who receive very good grades is 9 teachers, or 90%.